Prevention On Trafficking In Persons And Smuggling Of Migrant In Malaysia: Enforcement And Laws - Ajiman, Reseman; Rahim, Rohani Abdul; Landa, Azizah; Intung, Rovina; Makanah, Herlina (Universiti Sains Malaysia, 2016)

(untitled)
The issue on trafficking in persons and smuggling of illegal migrants in Malaysia is increasingly crossborder crime that poses a worrying situation. Trafficking in persons and smuggling of migrants terms often confused the public generally. The differences in its terms and understanding on these issues must be determined and important in providing relevant in treatment and legal protection in Malaysia. In addition, forced labor rights as workers are often overlooked by the authorities because of their status as illegal immigrants (PATI). This complicate matter further when national legislation in particular the Anti-Trafficking in Persons and Anti-Smuggling of Migrants (ATIPSOM) Act 2007 [Act 670] also does not state clearly the interpretation of the Act. According to court cases decided in Malaysia, it is found that the courts interpret a situation as 'trafficking in persons' based on its purpose and forms of exploitation outlined in the Act.